1997
DOI: 10.1002/art.1780400619
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of major histocompatibility complex allelic associations with systemic lupus erythematosus in Taiwan

Abstract: Objective. To investigate the association of HLA class I1 alleles/haplotypes, type I C2 deficiency gene, and tumor necrosis factor a gene promoter allele (TNF2) with systemic lupus erythematosus (SLE) in the Chinese population in Taiwan.Methods. The HLA-DRB1 and DQBl alleles were studied in 105 SLE patients and 115 controls by the polymerase chain reaction (PCR)/sequence-specific oligonucleotide probe method, the subtyping of DRB1*15/16 and DRB5 by PCR with sequence-specific primers, type I C2 deficiency gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
33
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 33 publications
4
33
5
Order By: Relevance
“…Complex factors are thought to play various roles in the pathogenesis of SLE. For instance, serological studies have long suggested an association between certain human leukocyte antigens and SLE or autoantibody production [13, 14, 15, 16]. On the other hand, it is still controversial which cytokines play roles in the pathogenesis of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Complex factors are thought to play various roles in the pathogenesis of SLE. For instance, serological studies have long suggested an association between certain human leukocyte antigens and SLE or autoantibody production [13, 14, 15, 16]. On the other hand, it is still controversial which cytokines play roles in the pathogenesis of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the ethnic background of the study populations and the assay techniques, a wide variety of associations has been described. In Caucasians, the most consistent positive class II major histocompatibility complex (MHC) association with SLE is HLA-DR3 (1-6), whereas in Asian populations, HLA-DR1 and DR2 haplotypes predominate (7)(8)(9).…”
mentioning
confidence: 99%
“…This is strongly supported by the linked association of genes encoded within the H-2 z locus with susceptibility to lupus in several mouse models, including New Zealand hybrid mice and their derivatives (5,6). The disease association with certain HLA haplotypes, including HLA-DR2 and HLA-DR3 (7)(8)(9)(10)(11) and HLA-B8 (11), and certain complement (12) and TNF polymorphisms (13) has been reported in human lupus.…”
mentioning
confidence: 99%